5 Years Experience in Intracapsular Femoral Neck Fracture Management - Khudair, Ali H (AL-Kindy College Medical Journal, 2007)
Background: Displaced intracapsular fracture of the femoral neck remain a challenging issue despite the advancement in the ways of treatment .The purpose of this study is to assess the results of different methods of treatment in different age groups. Methods: This study was conducted over a period from (1998-2004) on 26 patients, with ages of 5 – 85 years with intracapsular fracture of the femoral neck due to different insults in Tikrit teaching hospital. Open reduction and internal fixation was done to those patients of<60 years of age, while uncemented Austin-Moore hemiarthroplasty was conducted in patients of >60 years old. Patients were followed for 6-12 months for any complication. Results: The main age group among the patients were those >60 years [13 (50%)]. The main cause of fracture was fall from standing position in 19 (73%), were treated by uncemented Austin-Moore prostheses. The main complications were hip and knee pain [8(30.7%) and5 (19.2%)] respectively. Non-union (11.5%) and avascular necrosis (11.5%) was the commonest complications in young patients, and were treated by internal fixation especially if the time of surgery was delayed over 24 hours. Conclusion: The reduction and internal fixation will continue to be used as the primary treatment of displaced intracapsular fracture in many younger patients because the benefits of preservation of the normal hip joint which should be done urgently within the first 24 hours. However, if this method of treatment is unsuccessful and requires revision, the risk of early complications is higher and hip function is poor. When hemiarthropla